OPTIMALISASI PLATFORM DIGITAL DALAM MENINGKATKAN PEMASARAN DAN PENGELOLAAN KEUANGAN PETANI HIDROPONIK DI SOREANG, KABUPATEN BANDUNG - Rizka Noristaman; Yesi Suhartini, Yusnaini , Deasy Sandya, Andri Asmari , R.Arif Nugraha, Diki Iskandar, Adrie Charvia (Adiba Aisha Amira, 2025)
The Community Service activity (PKM) themed ‘Optimisation of Digital Platforms in Improving Marketing and Financial Management of Hydroponic Farmers in Soreang, Bandung Regency’ in collaboration with the ‘Baraja Hydrofarm - Central Hydroponic South Bandung’ community aims to help hydroponic farmers overcome the challenges they face in marketing and business management. In the growing digital era, the utilisation of information technology such as marketplaces and financial management applications has become very important to improve the efficiency and competitiveness of farmers. This activity began with the preparation of training materials and socialisation to the farming community, followed by training in digital marketing and financial management. The methods used included interactive lectures, technical simulations, and group discussions. The results of this activity showed a significant improvement in participants' skills in using social media and marketplace platforms to promote their products. In addition, participants were also able to compile simple financial reports that helped them in cash flow management and production cost calculation. The evaluation showed that participants are committed to continue adopting digital technology in their businesses. The programme was quite successful in improving farmers' technical skills and expanding the marketing network of the Baraja Hydrofarm community. Recommendations for the sustainability of the programme include expansion of the training, development of modules with the latest technology, and periodic evaluation to ensure continued adoption of the technology. It is hoped that this programme can positively contribute to local economic development as well as the welfare of hydroponic farmers in other regions.